Construção dos quadrados mágicos e aplicação na criptografia como ferramentas educacionais - Oliveira, Eustáquio Morais (2023)
This project investigates the use of magic squares and educational robotics in teaching and learning mathematics as a motivator for students. The application of robotics, more specifically, the creation and assembly of practical experiences in the laboratory, which allows development in a playful way, can promote interaction between concepts and applications. Education is a prolific field for the use of technology, in view of the set of possibilities it presents, making learning more dynamic and motivating. Based on this observation, magic squares and educational robotics is a learning proposal in which students apply the scientific method and develop skills, competences, critical capacity, a sense of knowledge to overcome difficulties in solving. Thus, the current work aims to investigate the use of magic squares combined with Educational Robotics as a pedagogical resource. We will also highlight the importance of the use of technology in education, basing the work on the visions of some renowned authors of the present time, we will historically define the magic square and describe the mindstorms educational kit 9797 used for this project. With regard to the acquisition of knowledge, the main evidence of the research was that the pedagogical work, guided by the basic assumptions described in the theoretical framework, effectively favored the students’ learning.